2015
DOI: 10.1039/c5nr04129e
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the growth and composition evolution of gold-seeded ternary InGaAs nanowires

Abstract: InGaAs nanowires offer great promise in fundamental studies of ternary compound semiconductors with variable composition and opens up a wide range of applications due to their bandgap tunability and high carrier mobility. Here, we report a study on the growth of Au-seeded InGaAs nanowires by metal-organic vapour phase epitaxy and present a model to explain the mechanisms that govern the growth and composition evolution in ternary III-V nanowires. The model allows us to further understand the limitations on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(81 citation statements)
references
References 35 publications
4
76
1
Order By: Relevance
“…The axial NW heterostructure has been regarded as one of the key benefits of NWs compared to planar layers because strain can be elastically relaxed via the free surfaces, thus reducing defects such as dislocations when there is a lattice mismatch. Although the flexibility even for axial heterostructures is not endless and misfit dislocations eventually will form, there are unique possibilities for new defect-free material combinations compared to planar growth such as InAs-InSb, GaAs-GaSb, InAs-GaSb, GaAs-InAs, GaAs-InGaAs, InP-InGaP, GaP-InGaP, and InAsP-InP. ,, The main purposes for growing these heterostructures ranges from creating a transition from a substrate material into a desired active device material, creating an active part of a device by promoting tunnelling at a staggered bandgap heterostructure interface or for creating quantized structures used in for example infrared photodetectors (see Figure i–m). ,, However, when growing ternary alloy materials such as In x Ga 1– x As and In x Ga 1– x P, where alloy mixing occurs on the group III sublattice, it is important to consider the implications the growth will have on the full 3-D NW structure. For example, it has been observed that composition can vary in the axial , as well as the radial direction due to the difference in group III adatom diffusion lengths.…”
Section: Iii–v Nanowire Growth and Devicesmentioning
confidence: 99%
“…The axial NW heterostructure has been regarded as one of the key benefits of NWs compared to planar layers because strain can be elastically relaxed via the free surfaces, thus reducing defects such as dislocations when there is a lattice mismatch. Although the flexibility even for axial heterostructures is not endless and misfit dislocations eventually will form, there are unique possibilities for new defect-free material combinations compared to planar growth such as InAs-InSb, GaAs-GaSb, InAs-GaSb, GaAs-InAs, GaAs-InGaAs, InP-InGaP, GaP-InGaP, and InAsP-InP. ,, The main purposes for growing these heterostructures ranges from creating a transition from a substrate material into a desired active device material, creating an active part of a device by promoting tunnelling at a staggered bandgap heterostructure interface or for creating quantized structures used in for example infrared photodetectors (see Figure i–m). ,, However, when growing ternary alloy materials such as In x Ga 1– x As and In x Ga 1– x P, where alloy mixing occurs on the group III sublattice, it is important to consider the implications the growth will have on the full 3-D NW structure. For example, it has been observed that composition can vary in the axial , as well as the radial direction due to the difference in group III adatom diffusion lengths.…”
Section: Iii–v Nanowire Growth and Devicesmentioning
confidence: 99%
“…In the case of L = 0 μm, the incident light was almost completely reflected and there was a small absorption resonance (∼4%) caused by surface plasmon resonances (Figure S4a in the Supporting Information), which indicates that the AuNPs (including Au alloys at the top of the SiNWs) had a small effect on the reflection measurements. Therefore, based on the diameter-dependence of the nanophotonic resonances, we attribute the aforementioned red-shift of λ max to the slight increase in the SiNW diameter from 200 to 220 nm owing to VS growth (Figure d) . In addition, the above increase in absorption resonance with increasing SiNW length can be elucidated by the equation R = R sub exp­(−2α eff L ) .…”
Section: Resultsmentioning
confidence: 87%
“…Therefore, based on the diameterdependence of the nanophotonic resonances, we attribute the aforementioned red-shift of λ max to the slight increase in the SiNW diameter from 200 to 220 nm owing to VS growth (Figure 2d). 38 In addition, the above increase in absorption resonance with increasing SiNW length can be elucidated by the equation R = R sub exp(−2α eff L). 39 In this equation, R sub and α eff represent the reflection at the Si substrate interface and the effective absorption coefficient of the SiNW array, respectively, and L is the length of the NW.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The top part of the nanowire near the Au seed, i.e., the last segment to grow, was observed to be In-rich due to precipitation from the Au-alloy particle during cool down. Compositional gradients in ternary nanowires have been previously observed by many groups, since these gradients can be readily measured by EDS.…”
mentioning
confidence: 82%